ANALYSIS ON METHODS OF DETERMINING HALAL OR HARAM OF ANIMALS TO BE EATEN ACCORDING TO SYEIKH ABDUL MALIK BIN ABDULLAH IN HIS KITAB AL-KIFAYAH - Zurita, Mohd.Yusoff; Rahimah, Embong (2014)
Kitab al-Kifayah is a Malay manuscript which contains the debate about Islamic doctrine (aqidah) and Islamic jurisprudence (Fiqh). It was composed in the 17th century or early 18th century by Syeikh Abdul Malik bin Abdullah, also known as Tok Pulau Manis. One of the chapters in this manuscript emphasizes matters pertaining to haram and halal animals are eaten. The issue of halal or haram regarding an animal has been debated among Muslim jurists (Fuqaha’). This happens because there are not many evidences from the Quran and the Hadith explain specifically about the ruling of eating a certain type of animals. As a consequence, this paper aims to identify what are the methods used by Syeikh Abdul Malik in determining halal or haram in eating an animal. It also analyzes the methods proposed by him in al-Kifayah. In order to meet these objectives, documentation method used by examining three copies of the Kitab al-kifayah discovered by the researchers. The results of this study demonstrate the methods proposed by Sheikh Abdul Malik is compatible with what are outlined by the legal scholars in the authoritative books of al-Shafii. However, he was not merely citing and translating what are in the scriptures, but also he was able to develop his own method for the categories of birds which are grabbing and holding food with their mouths, eating nails, breathing while drinking water and birds marked at their neck.